Prevalence of different approaches to remuneration in the Czech Republic - Kateřina Procházková; Peter Mičák (Trends Economics and Management, 2022)
Purpose of the article: The presented paper analyses the application of different methods and approaches to the remuneration of senior executives in the manufacturing industry. Methodology/methods: The presented article is based on a combination of the analysis of case studies, annual reports, and primary research consisting of in-depth interviews and a questionnaire survey. Scientific aim: The paper analyses the prevalence of three different remuneration methods for senior executives. The first is the remuneration through option and stock programs, the second is the value-based approach to remuneration, and the last is the remuneration linked to traditional indicators such as company earnings. Each of these methods has advantages and disadvantages described in the paper. Findings: The limiting factor for more significant deployment of senior executives' remuneration through option and stock programs is, above all, the low level of development of the capital market in the Czech Republic. Another analysed method of remuneration is to link it with the Economic Value Added indicator, i.e. with the so-called value-added approach to remuneration. Unfortunately, this approach is not very widespread due to the necessary complex change of accounting data. The authors' research results suggest that the most common remuneration of senior executives is based on a traditional connection with the company's earnings, which is often considered inappropriate and outdated nowadays. Conclusions: Our research implies that the most prevalent senior executives' remuneration in the Czech Republic is linked to indicators that can often be described as outdated nowadays. Therefore, the paper describes the possible reasons for using these indicators.
Keywords: M15; M21; 650; Remuneration; Contract Theory; Senior Executive; Bonus Bank; Economica Value Added; Earnings